Synthesis, Docking Studies and Pharmacological Activity of Synthetic Flavonols - Mohammad Shoaib (Science Faculty of Chiang Mai University, 2019)
Diabetes is a group of metabolic disorders characterized by hyperglycemic condition from defects in insulin secretion, insulin action, or both. The chronic hyperglycemia of diabetes is coupled with long-term dysfunction, damage and even failure of different vital organs, like kidneys, nerves, eyes, heart and the blood vessels. Biologically flavonol derivatives were synthesized via Claisen-Schmidt condensation of ketones with different aldehydes in a good yield (%) for their antidiabetic potentials. The structures were established by different spectroscopic techniques like 1H NMR, 13C NMR, IR and elemental analysis. The findings showed that substituted flavonols showed significant in-vitro enzyme inhibitions, molecular docking and in-vivo antidiabetic activities are potential candidates for the treatment of diabetes.The electron donating attached methyl derived flavonol (OF2) showed promising activity on á-amylase (IC50 = 59.96±2.09 mg/mL respectively) in comparison with electron withdrawing group halogen to flavonol (OF3, IC50 = 70.19±2.26 mg/mL respectively) and simple flavonol (OF1) with (IC50 = 71.34±1.63 mg/mL). Administration of the OF1 at a dose of 100 mg/kg caused a significant (**P < 0.01, n = 8) reduction in the level of blood glucose compared to diabetic control on 15th, 21st and 28th day. OF2 in a dose of 100 mg/kg decreased blood glucose level from 253.8 to 180.7 mg/dl from 7th day onwards to 28th day (**P < 0.01, n = 8 for 7th and 15th day and ***P < 0.001, n = 8 for 21st and 28th day). The effect of OF3 was almost similar to OF1.